From paper to practice: An evaluation of the impact of the 1989 NACI guidelines for universal hepatitis B screening in pregnancy. - Seviour, Rosann. (University of Ottawa (Canada), 1996)
The development and release of clinical practice guidelines continue unabated. Yet the question remains: do practice guidelines guide practitioners? This study examines the implementation of guidelines published by Canada's National Advisory Committee on Immunization (NACI) on hepatitis B screening in pregnancy. Hepatitis B is transmitted to infants from their chronic carrier mothers during the perinatal period. Asymptomatic HBsAg positive mothers are at risk of transmitting their infection to their newborns at a rate of 20 to 30%. Mothers who are also HBeAg positive transmit the infection at a rate of 70-90%. Ninety percent of infants infected in the perinatal period will become chronic carriers. Such infants have an increased risk for chronic active hepatitis, cirrhosis and hepatocellular carcinoma. Twenty-five percent will die of chronic liver disease in early adulthood. The use of hepatitis B immune globulin and vaccine after birth can prevent up to 90% of hepatitis B infections in infants. Successful immunoprophylaxis of an infant requires that her carrier mother be identified prior to giving birth. In 1989, after years of recommending screening on a selective high risk basis, NACI recommended screening all pregnant women for hepatitis B surface antigen (HBsAg). If testing was not done during pregnancy it was to be done at the time of delivery.
Keywords: Health Sciences, Obstetrics and Gynecology.